Interaction of Alpha-Synuclein With Lipids: Mitochondrial Cardiolipin as a Critical Player in the Pathogenesis of Parkinson’s Disease - Gilmozzi, Valentina; Gentile, Giovanna; Castelo Rueda, Maria Paulina; Hicks, Andrew A.; Pramstaller, Peter P.; Zanon, Alessandra; Lévesque, Martin; Pichler, Irene (Frontiers in Neuroscience, 2020)
Alpha-Synuclein (α-Syn) is a central protein in the pathogenesis of synucleinopathies, a group of neurodegenerative disorders including Parkinson’s disease (PD). Although its role in neurotransmission is well established, the precise role of this protein in disease pathogenesis is still not fully understood. It is, however, widely regarded to be associated with the misfolding and accumulation of toxic intracellular aggregates. In fact, α-Syn is the most abundant protein component of Lewy bodies and Lewy neurites, which are also characterized by a high lipid content. Lipids, the main constituents of cellular membranes, have been implicated in many aspects of PD-related processes. α-Syn interacts with membrane phospholipids and free fatty acids via its N-terminal domain, and altered lipid-protein complexes might enhance both its binding to synaptic and mitochondrial membranes and its oligomerization. Several studies have highlighted a specific interaction of α-Syn with the phospholipid cardiolipin, a major constituent of mitochondrial membranes. By interacting with cardiolipin, α-Syn is able to disrupt mitochondrial membrane integrity, leading to mitochondrial dysfunction. Additionally, externalized cardiolipin is able to facilitate the refolding of toxic α-Syn species at the outer mitochondrial membrane. In this review, we discuss how α-Syn/lipid interactions, in particular the α-Syn/cardiolipin interaction at the mitochondrial membrane, may affect α-Syn aggregation and mitochondrial dysfunction and may thus represent an important mechanism in the pathogenesis of PD.